Experiencing Rural Morocco Through Healthcare - Lydia George; Dr. Amy Way (Undergraduate Research Journal for the Human Sciences, 2016)
An international service-learning program to Morocco consisted of students and faculty from Lock Haven University and was conducted in 2009, 2010, 2012, and 2014 for a week at a time. Data was collected from different populations in Morocco and was analyzed based on the populations’ height, weight, BMI, blood pressure, and chief complaints. The populations were then compared to each other, to the national health of Morocco, and to the United States.
Keywords: Morocco; Healthcare